ANALISA MIKROTIK SEBAGAI FILTER JARINGAN DAN PENGATURAN BANDWIDTH MANAJEMEN HOTSPOT PADA UNIVERSITAS ISLAM KEBANGSAAN INDONESIA(UNIKI) - Mutasar; Muhammad Aziz (LPPM-UNIKI, 2020)
The internet that is stable and safe from interference in one network has become a necessity for every user of the internet network both through mobile phones and computers. Hotspot and LAN need bandwidth management, so when accessingthe internet simultaneously it is no longer a problem. In addition, network security can be filtered through proxy so that online sites and games that do not need to be accessed during lecture hours from 8:00 a.m. until 5:00 p.m. can be blocked and reactivated after finishing college. By implementing network filters, the internet on the campus in Universitas Islam Kebangsaan Indonesia (UNIKI) will be stable and safe during lecture hours as expected.Keywords: MikroTik, HotSpot, Bandwidth,UNIKI